Developing Islamic science based integrated teaching materials for Islamic religious education in Islamic high schools - Suparjo, Suparjo; Hanif, Moh; Senja, Dimas Indiana (Pegem Journal of Education and Instruction, 2021)
This study aims to develop valid and reliable Islamic Education (PAI) teaching materials based on integrative Islamic science in Class X of Islamic High School in Indonesia. This research uses Borg & Gall’s research and development model. The results showed that the content and construct validity of the teaching materials for Islamic Education based on integrative Islamic science in Class X of Islamic Senior High School are valid and qualified for factor analysis. The teaching materials for Islamic Education meet reliability criteria. The feasibility level of Islamic Religious Education Integrative Islamic Science Class X of Islamic Senior High School is determined by four product assessment activities; material expert validation, media expert validation, limited trials, and readability trials. The results of the validation of material experts from 8 aspects of the assessment obtained on average 3.33 and classified as "Excellent", the validation results of media experts from 7 aspects of the assessment obtained on average 3.23 with "Good" classification, limited trials of 2 aspects of the assessment obtained an average of 3.54 classified as "Excellent" and the legibility trials of the 2 aspects of the assessment obtained an average of 3.60 with "Excellent" classification. The total average is 3.43 in the "Excellent" classification.